Development of an optimised physiotherapist-led treatment protocol for lateral elbow tendinopathy: a consensus study using an online nominal group technique - Chris Littlewood; Marcus Bateman; Jonathan C Hill; Benjamin Saunders (BMJ Open)
Objectives There are a wide range of physiotherapy treatment options for people with lateral elbow tendinopathy (LET); however, previous studies have reported inconsistent approaches to treatment and a lack of evidence demonstrating clinical effectiveness. This study aimed to combine the best available research evidence with stakeholder perspectives to develop key components of an optimised physiotherapist-led treatment protocol for testing in a future randomised controlled trial (RCT).Design Online consensus groups using nominal group technique (NGT), a systematic approach to building consensus using structured multistage meetings.Setting UK National Health Service (NHS).Participants 10 physiotherapists with special interest in LET, 2 physiotherapy service managers and 3 patients who had experienced LET.Interventions Two consensus groups were conducted; the first meeting focused on agreeing the types of interventions to be included in the optimised treatment protocol; the second meeting focused on specific details of intervention delivery. Participants were sent an evidence summary of available treatments for LET prior to the first meeting. All treatment options were discussed before anonymous voting and ranking of priority. Consensus for inclusion of each treatment option was set at ≥70% based on OMERACT guidelines. Options with 30%–69% agreement were discussed again, and a second vote was held, allowing for a change of opinion.Results The optimised physiotherapist-led treatment package included: advice and education, exercise therapy and orthotics. Specific components for each of these interventions were also agreed such as: condition-specific advice, health-promotion advice, exercise types, exercise into ‘acceptable’ levels of pain, exercise dosage and type of orthoses. Other treatment options including electrotherapy, acupuncture and manual therapy were excluded.Conclusion An optimised physiotherapist-led treatment protocol for people with LET was successfully developed using an online NGT consensus approach. This intervention is now ready for testing in a future pilot/feasibility RCT to contribute much needed evidence about the treatment of LET.Trial registration number This is the pre-cursor to the OPTimisE Pilot and Feasibility Randomised Controlled Trial. Registration: https://www.isrctn.com/ISRCTN64444585